54.0k views
13 votes
(cosec a + 1)*(1 - sin a)= cos a* cot a

User Llaves
by
5.0k points

1 Answer

5 votes

Answer:

See proof below

Explanation:

Given the equation, we are to prove that it is true

(cosec a + 1)*(1 - sin a)= cos a* cot a

From LHS

(cosec a + 1)*(1 - sin a)=

Expand

cosec a - cosecasina + 1 - sina

Since cosec a = 1/sina

1/sina - (1/sina)sina + 1 - sina

1/sina - 1 + 1 - sina

1/sin a - sina

Find the LCM

1-(sin^2a)/sina

cos^2a/sina

cosa * cosa/sina

cos a * cot a (which gives the RHS)

User Avarkx
by
5.3k points